Core Inflation in Selected European Union Countries - Christine Gartner; Gert Wehinger (Oesterreichische Nationalbank (OeNB), 1998)
We calculate core inflation indicators for Austria, Belgium, Finland, France, Germany, Italy, the Netherlands, Sweden and the United Kingdom using two structural vector-autoregression (SVAR) models. In the first one we use out-put and prices to identify supply and demand shocks by long-run identifying restrictions, for the second one we add short-term nominal interest rates to capture effects of monetary disturbances. Core inflation is then defined as driven by demand and, respectively, monetary shocks. Comparing our results to other studies we conclude that the resulting core inflation indicator can be regarded as helpful for monetary policy.
Keywords: 330